Mechanism of fat, oil and grease (FOG) deposit formation in sewer pipelines - Husain, Iman A. F.; Al-Khatib, Ma'an Fahmi Rashid; Hoda, Asif; Jami, Mohammed Saedi; Mirghani, Mohamed Elwathig Saeed; Zainudin, Zaki (2013)
The release of fat, oil, and grease (FOG) into collection systems results in the blockage of pipes and subsequent sanitary sewer overflows (SSOs). Currently,municipalities such as Indah Water Consortium (IWK) who are responsible for maintaining these collection systems have little guidance as there is a substantial lack of scientifically-based information regarding the mechanism of FOG deposition and the effective control method of FOG. In this study, the mechanism of FOG deposit formation is investigated by samples characterization. Sewage flow laden with FOG is also modelled using ANSYS CFX. The results showed that the deposits mainly constitute of FOG while there is a high amount of Palmatic and Oleic acids which indicate the preference for hydrolysis reaction.